An overall study on efficient Cr (VI) adsorbents for improving of the application value of Chlorella pyrenoidosa - Yi-Tong Wang; Liang-Yi Zhang; Le-Le Kang; Ya-Jun Wang; Jun-Guo Li; Hang Zhao; Kai-Li Dong; Hong-Peng Li; Xuan Guo; Ren-Long Dong; Ming-Ming Chen; Zhen Fang (Ecotoxicology and Environmental Safety)
Chromium (Cr) is one of the most common pollutants in aquatic ecosystems, posing a serious threat to environmental protection and biological survival. In this study, the adsorbents, prepared from the residue of extracting lipids, polysaccharides and proteins from Chlorella pyrenoidosa, are investigated for effectively purring the Cr (VI)-containing wastewater. The lipid, polysaccharide and protein are identified to having potential for the preparation of biodiesel, food component substitution and feed production, respectively. Meanwhile, Cr (VI) adsorbents are achieved from these extracted residues. The results show that a porous structure with sufficient active functional groups (O-H, pyrrole N, CO, C-O-C, C-O and pyridine N) and remarkable surface area can be well realized. All active functional groups present the effective adsorption performance for removing the Cr (VI) ions from the wastewater due to their active negative adsorption energies, especially -OH and pyrrole N (O-H = −2.86 eV > pyrrole N = -2.80 eV > CO = −2.30 eV > C-O = −2.16 eV > C-O-C = −2.14 eV > pyridine N = -1.87 eV). Under the conditions of high Cr (VI) concentration of 300 mg/L, the amount of absorbent needed for adsorption is reduced from 8 g/L (original algal residue) to 4 g/L (modified biochar). And removal rate of Cr (VI) is dramatically increased from 60.94 % (L), 60.57 % (S) and 46.48 % (P) to 98.99 % (LC800K2), 96.39 % (SC800K2) and 94.73 % (PC800K2). This study provides an achievable approach for the comprehensive utilization of Chlorella pyrenoidosa from extracting valuable biomass to effectively treating Cr (VI)-containing wastewater.